Effects of employees living with an ‘arthritis’ on sickness absence and transitions out of employment: a comparative observational study in the UK - William Whittaker; Ross Wilkie; James Higgerson; Katherine Payne; Martin Eden; Suzanne MM Verstappen (RMD Open)
Purpose To assess sickness absence and transitions from employment for employees with arthritis compared with employees without arthritis over time.Methods We use 10 waves of the UK Household Longitudinal Survey (2009–2019). The sample (n=38 928) comprises employees aged 50 years to state retirement age. Arthritis was self-reported and could refer to people with conditions under the umbrella term ‘inflammatory arthritis’ or osteoarthritis (hereafter ‘arthritis’). Weighted random-effects multivariable linear probability models were estimated for two employment-related measures (1) sickness absence and (2) transitions from employment to: (a) unemployment; (b) long-term sick; (c) early retirement. These were regressed against a variable for arthritis and confounding factors (age, socioeconomic job classification, employing sector, year and additional health conditions). Additional analyses examined an interaction between the variable arthritis and these factors to test whether the effect of arthritis differs between these groups.Results Employees reporting having arthritis were more likely to have sickness absence (1.35 percentage points greater rate (95% CI (0.92, 1.78)) and to transition to long-term sick (0.79 percentage points (0.46, 1.13)) and early retirement (0.58 percentage points (0.05, 1.11)). No effect was found for transitions to unemployment. There was limited evidence that the effects of arthritis vary for employees in different socioeconomic classifications.Conclusions Employees living with arthritis have higher rates of sickness absence and greater rates of transitions from employment to long-term sick and early retirement. Further work could look at ways to quantify the implications for individuals, employers and the state and ways to alleviate the effects of living with arthritis on work participation.